Anekdot Bahasa Ende, Desa Rukuramba, Kabupaten Ende - Zaenab Jamaludin; Maria Floriana Serlin (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
The purpose of this research is to introduce Ende's culture in the form of anecdotes, which some teenagers today have never recognized an anecdote from the area where they were born. This is if we continue to let the Anecdote, as one of the cultural heritages of Ende in the form of Oral Literature, will eventually become extinct. They know the Anecdote from the Indonesian version. The approach used is a qualitative approach because the data collected is in the form of verbal words that are systematic and not in the form of statistical numbers. The method chosen in this study is the listening and speaking method, and the techniques used in this study are the recording technique, the note-taking technique and the listening technique. Data were analyzed based on the interactive model developed by Miles and Huberman, which includes four components, namely, data collection, data reduction, data display and conclusion /verification. The results show that in the Ende language anecdote there are many meanings and moral messages that we can make as guidelines for family life and social interaction in the community environment.